The concept of different types and forms of speech - Kamenchuk A. I. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2023)
Speech, both in Russian and in speech psychology, has not lost its relevance over a long history. Speech was given the highest importance as writers, speech therapists, as well as contemporaries of psychology. This article will consider the concepts of different types and forms of speech, as well as the concept and content of oral and written speech. The features and distinctive features are revealed.
Keywords: русский язык; психология; письменная речь; грамматика; речь; speech; psychology; устная речь; Russian language; written speech; grammar; oral speech